2007
DOI: 10.1007/s11274-007-9599-9
|View full text |Cite
|
Sign up to set email alerts
|

Mn2+ enhances theanine-forming activity of recombinant glutamine synthetase from Bacillus subtilis in Escherichia coli

Abstract: Bacillus subtilis glutamine synthetase (GS) was highly expressed (about 86% of total protein) as soluble protein in Escherichia coli BL21(DE3) containing pET28a-glnA, which was induced by 0.4 mM IPTG in LB medium, and maximal theanine-forming activity of the recombinant GS induced in LB is 6.4 U/mg at a series concentration (0-100 mM) of Mn 2+ at optimal pH 7.5. In order to get GS with high theanine-forming activity, safety, and low cost for food and pharmaceutics industry, M9-A (details are described in ''Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…75 The recombinant GS exhibited the same properties and 30-fold higher enzyme productivity compared to that of original P. taetrolens Y-30. 75 In addition, the GSs from Bacillus subtilis, 76 Pseudomonas fluorescens, 77 and Bacillus megaterium 78 were also investigated and characterized to possess the capability of synthesizing Ltheanine.…”
Section: Methods For L-theanine Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…75 The recombinant GS exhibited the same properties and 30-fold higher enzyme productivity compared to that of original P. taetrolens Y-30. 75 In addition, the GSs from Bacillus subtilis, 76 Pseudomonas fluorescens, 77 and Bacillus megaterium 78 were also investigated and characterized to possess the capability of synthesizing Ltheanine.…”
Section: Methods For L-theanine Productionmentioning
confidence: 99%
“…taetrolens Y-30 . In addition, the GSs from Bacillus subtilis, Pseudomonas fluorescens, and Bacillus megaterium were also investigated and characterized to possess the capability of synthesizing l -theanine.…”
Section: Methods For L-theanine Productionmentioning
confidence: 99%
“…The enzyme glutamine synthetase and related enzymes, originating from Escherichia coli ,60 Pseudomonas taetrolens ,61 Methylovorus mays 62 and Bacillus subtilis ,63 have been utilised for the synthesis of theanine from glutamic acid and ethylamine. Unlike the glutaminase biosynthetic pathway discussed previously, this glutamic acid transformation, while using a cheaper and more stable starting material, requires a continuous supply of ATP to drive the reaction 62.…”
Section: Chemical Synthesis and Biosynthesis Of Theaninementioning
confidence: 99%
“…Wu et al identified 20 CsGS genes, including several unconfirmed CsTSs . Studies on bacteria, C. sinensis , and pea seeds have shown that GS can convert Glu and free ammonia to Gln, and also transfer Glu to l -theanine in the presence of ethylamine. , These findings suggest that GS and TS are very similar not only in their DNA sequences, but also in their enzymatic activities. As GS/TS are present in many plants, it is still unknown why l -theanine accumulates only in C. sinensis , and barely or not at all in other plant species.…”
Section: Introductionmentioning
confidence: 99%